Failure Prediction of Cracked Pressure Vessel under Fatigue Load Based on API 579 Standard and Finite Element Method - Akbar, Musthafa (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
Failure prediction of cracked pressure vessel is analyzed based on crack growth behavior under fatigue loading. The major objective of this study was to investigate and validate the use of commonly used industry standard with finite element method in order to predict failure of cracked pressure vessel. Growing of crack due to fatigue load was analyzed using both analytical and finite element method. In analytical side, API 579 Code is used with involving safety and correction factor which will increase conservatism degree of the results. Pressure vessel with D/t ratio 40, 60, and 80 were taken into analysis. Semi elliptical cracks in longitudinal and circumferential position were included into analysis with ratio a/t=0.3, 0.5, 0.8 and a/c=0.15, 0.125, 0.1. In this paper, there are 84 numerical model were solved numerically and plotted into several curves. Comparisons between API 579 and finite element simulation show that pressure vessel with D/t=40, 60 and 80 have percent error about 2.16 %, 9.32 % and 10.57 %, respectively. This results are reasonable due to several safety factor are included in API 579 analysis. Results of this paper can be used as consideration for make a decision regarding to integrity analysis of pressure vessel.